Efektifitas Pemberian Elemen Penghangat Cairan Intravena Dalam Menurunkan Gejala Hipotermi Pasca Bedah Sectio Caesar Di Ruang Recovery Room RSUD Toto Kabila Kabupaten Bone Bolango - Pakaya, Amelia; Ayuba, Asni (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: : Cesarean section surgery can cause physiological changes in the body such as decreased body temperature or hypothermia. In patients after cesarean section surgery, the incidence of shivering is as a compensatory mechanism of the body against hypothermia. Methods: : The research used in this study was Pre-experimental research with a one-group pre-post test design approach, the number of samples in this study was the same as the population of 10 respondents. Results: The results showed that the administration of intravenous fluid warming elements was effective in reducing symptoms of hypothermia after cesarean section surgery in the recovery room of Toto Kabila Hospital, Bone Bolango Regency with a significant value or PValue of 0.002 <0.05. Conclusion: : : It is hoped that it can add information for other health workers related to body temperature after surgery such as sc surgery and how to handle it.